Plasmonic behavior of ionic liquid stabilized gold nanoparticles in molecular solvents - Thawarkar, Sachin; Thombare, Balu; Khupse, Nageshwar D. (New Journal of Chemistry, 2017)
In this paper, we have demonstrated the facile synthesis of stable gold nanoparticles (AuNPs) using imidazolium ionic liquids (ImILs) as a stabilizer as well as a surfactant and their surface plasmon resonance (SPR) in different molecular solvents with varying dielectric properties. The preparation of AuNPs capped with N,N'-dialkyl ImILs of different chain lengths (denoted as [C-4, C-n-im]Br, n = carbon number of the alkyl chain) has been investigated. With one long alkyl chain (n >= 14), these AuNPs could be stably dispersed in solution over a month. The amphiphilic nature of the imidazolium salt dictates the stability and dispersion of these AuNPs in organic or aqueous solvents. Alkyl chain lengths (n >= 14) and the amount of ImILs have insignificant effect on the size of AuNPs and they possess an average size of 5 nm. These ionic liquid stabilized AuNPs were exploited to examine their optical properties when exposed to various solvent systems by measuring the change in the SPR spectrum. It was seen that the position of the SPR band of AuNPs is greatly influenced by the solvents under consideration. The shift in the SPR absorption band is observed to be in the range of 520 nm to 605 nm for AuNP@[C-4,C-16-im]Br from nonpolar to highly polar solvents. The considerable discovery presented here is that the lambda(SPR) of the SPR shifts to the blue with the increase of carbon atom in the alcohol chain from methanol to 1-decanol. Also for polyethylene glycols (PEGs), the lambda(SPR) shifts to the blue with the increase in molecular weight from PEG 200 to PEG 600. In above both cases, the variation in SPR of AuNPs is observed according to the dielectric properties of the medium in addition to the steric factor of alcohols and PEGs during their interaction with AuNP surfaces.